Comparative study of modern CAT tools: Smartcat vs Matecat - Karpina, Olena (Волинський національний університет імені Лесі Українки, 2024)
This study investigates two cloud-based computer-assisted translation (CAT) tools, Smartcat and Matecat, focusing on their features, functionalities, and suitability for different translator profiles. It examones the historical evolution of CAT tools and their key components, including translation memories, glossaries, and quality assurance mechanisms. The comparison highlights the strengths and limitations of both tools, providing insights into their suitability for varied translation needs and levels of expertise.
Keywords: CAT-інструменти; CAT tools; машинний переклад; machine translation; Matecat; Smartcat